Wear-resistant light-cured polyurethane coating and application method thereof
By using two-component polyurethane coatings, combined with aqueous polyurethane/boron nitride composites and ion-loaded porous titanium dioxide, the gradient structure coating is designed to solve the problem of insufficient wear resistance in high wear scenarios, and achieve higher wear resistance and adhesion.
Patent Information
- Application Number
- CN202411662395.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The wear resistance of existing wood wear-resistant cured polyurethane coatings still need to be further improved in high wear scenarios.
Two-component polyurethane coating is used, component A includes aqueous polyurethane acrylate, aqueous polyurethane/boron nitride composite, photoinitiator and sodium lignin sulfonate, and component B contains porous titanium dioxide loaded with copper ions or zinc ions. Through the design of gradient structure coatings and the comprehensive utilization of fillers, the wear resistance of the coating is improved.
It significantly improves the wear resistance of the coating, enhances the adhesion and overall performance of the substrate, and is suitable for wood products in high wear scenarios.
Abstract
Description
Technical Field
[0001] The invention relates to the field of functional coatings, and in particular to a wear-resistant light-cured polyurethane coating and an application method thereof. Background Art
[0002] Wood is a traditional and widely used building and decoration material, and it has an irreplaceable position in furniture manufacturing, interior decoration, building facade decoration and other fields. Due to the porosity and relatively soft texture of wood itself, it is easily affected by wear, scratches and environmental factors (such as ultraviolet rays, humidity changes, etc.), which affects its aesthetics and service life. Photocuring technology is an efficient and environmentally friendly curing technology. Compared with traditional thermal curing technology, photocuring has the advantages of fast curing speed, low energy consumption, and low emission of volatile organic compounds (VOC) during the curing process. In the field of coatings, photocuring technology can quickly convert liquid coatings into solid coatings, greatly improving production efficiency. Polyurethane coatings have many excellent properties such as good wear resistance, flexibility, and chemical resistance. Combining polyurethane coatings with photocuring technology can give full play to the advantages of both and provide high-performance protective coatings for wood. This wear-resistant photocurable polyurethane coating for wood can form a tough, wear-resistant and beautiful protective film on the surface of wood, improving the quality and durability of wood products. Although the existing wear-resistant light-cured polyurethane coatings for wood have certain wear resistance, they still need to be further improved in some high-wear scenarios (such as wooden floors in public places, frequently used wooden furniture, etc.). Although the wear resistance of the coating can be enhanced by optimizing the molecular structure of polyurethane, introducing more wear-resistant functional groups, or adding nano-scale wear-resistant fillers (such as nano-silica, nano-alumina, etc.), the wear resistance of the coating still needs to be further improved. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a wear-resistant light-cured polyurethane coating, which is applied step by step and layer by layer on the surface of a substrate to obtain a wear-resistant polyurethane coating.
[0004] Technical solution: A wear-resistant light-cured polyurethane coating, wherein the polyurethane coating is a two-component polyurethane coating, and the two-component polyurethane coating comprises component A and component B, wherein component A is composed of the following components in parts by weight: 120-180 parts of waterborne polyurethane acrylate 40-60 parts of waterborne polyurethane / boron nitride compound Photoinitiator 2-5 parts Additives 0.5-3 parts Sodium lignin sulfonate 10-20 parts 40-70 parts of water; The component B is composed of the following important components: 5-10 parts of porous titanium dioxide loaded with copper ions or loaded with zinc ions Ethanol 90-100 parts; The waterborne polyurethane acrylate is any one or two of polyether waterborne polyurethane acrylate and polyester waterborne polyurethane acrylate; The photoinitiator is any one of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone or a mixture of more than one thereof; The auxiliary agent includes any one of a defoamer, a formaldehyde removal additive, an antibacterial additive, an anti-settling agent, a matting agent, a hand wax, and a dispersant, or a mixture of more than one of the above. Wherein, the preparation method of the waterborne polyurethane / boron nitride composite is: S11. Boric acid and urea are mixed in a mass ratio of 1:10-14 and added to water, heated in a water bath at 85-90° C. with stirring to obtain a BN precursor, and the BN precursor is reacted at high temperature to obtain flake boron nitride; S12. The flake boron nitride, urea and water were mixed and ball-milled at a speed of 500-800 r / min for 15-20 h. The mixed solution after ball milling was diluted and ultrasonically treated for 1-2 h, filtered and dried to obtain amino-modified boron nitride; S13. The amino-modified boron nitride is dispersed in acetone and uniformly dispersed by ultrasonication to obtain a boron nitride dispersion; S14. Mix polytetrahydrofuran ether diol and isophorone diisocyanate for reaction at a temperature of 90-95°C for 1.5-2.5 hours. After cooling to 80°C, add dihydroxymethylpropionic acid and 1,4-butanediol for reaction for 2 hours. Cool again to 70°C, add dibutyltin dilaurate dropwise for reaction for 3 hours to obtain a polyurethane prepolymer. Then add a boron nitride dispersion, react for 1-1.5 hours, and then cool to room temperature to obtain a waterborne polyurethane / boron nitride composite material. The method for preparing the porous titanium dioxide loaded with copper ions or loaded with zinc ions comprises the following steps: S21. Add tetrabutyl titanate to ethanol, stir and disperse evenly, then add water, continue stirring until the tetrabutyl titanate is completely hydrolyzed, and then add ammonium bicarbonate to the hydrolysis solution, the mass volume ratio of tetrabutyl titanate, ethanol, water and sodium bicarbonate is 2-4mL:10-20mL:50-100mL:1-2g, react at 170-190°C for 40-50h, and finally wash and dry to obtain nanoporous titanium dioxide powder; S22. The copper sulfate or zinc sulfate is added to a 0.5-1wt% aqueous solution of hydroxypropyl methylcellulose, and the mixture is stirred and dispersed to obtain a mixed solution, wherein the concentration of the copper sulfate or zinc sulfate in the mixed solution is 1-3wt%; S23. Add nanoporous titanium dioxide to the mixed solution in step S22, and after ultrasonic dispersion, filter and dry to obtain porous titanium dioxide loaded with copper ions or loaded with zinc ions. The application method of the above-mentioned wear-resistant light-cured polyurethane coating comprises the following steps: S1. The aqueous polyurethane acrylate in component A is added to water in parts by weight, and then the aqueous polyurethane / boron nitride complex, the photoinitiator and the additive are added successively, and the mixture is stirred to obtain a coating X; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, photoinitiator and additives are added, mixed and stirred to obtain coating Y; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z; S4. Apply coating X on the substrate at a coating amount of 45-125 g / m 2 After UV curing, the coating Y is applied to the substrate at a coating amount of 35-85g / m 2 Finally, the coating Z is applied and cured by ultraviolet radiation again to obtain a wear-resistant coating. Preferably, the substrate includes: wood board, stone-plastic composite floor; Among them, wooden boards include: a: solid wood flooring; b: any other core material, base material but with solid wood flooring as the surface layer; stone plastic composite flooring is: a solid base layer with a high-density, high-fiber mesh structure composed of stone powder, and the surface is covered with a wear-resistant polyurethane coating. Preferably, the parameters of the high temperature reaction in step S11 are: heating to 500-550° C. at 3° C. / min and keeping the temperature for 3 h. Preferably, in step S14, the molar ratio of isophorone diisocyanate, polytetramethylene ether glycol, dimethylol propionic acid and 1,4-butanediol is 5-10:1-2:1-2:2.6-5.5. Preferably, in step S14, the content of boron nitride in the polyurethane prepolymer is 12-16 wt %. Beneficial effects: The coating of the present invention has the following advantages: 1. The wear-resistant light-cured polyurethane coating of the present invention comprises two components A and B. When component A is applied to a substrate, a low-content waterborne polyurethane / boron nitride composite coating is applied to the bottom layer of the substrate, and a low-content filler coating has good adhesion to the substrate. A high-content waterborne polyurethane / boron nitride composite coating is applied to the outer side of the low-content waterborne polyurethane / boron nitride composite coating. The wear resistance of the coating can be improved by designing a gradient structure coating. 2. In the present invention, component B is coated on the outside of component A coating, and component B contains porous titanium dioxide loaded with copper ions or loaded with zinc ions. The copper ions or zinc ions of the porous titanium dioxide loaded with copper ions or loaded with zinc ions can be complexed with the sodium lignin sulfonate contained in component A to improve the adhesion and wear resistance of the overall coating. By introducing a variety of different types of fillers into the coating, the advantages of various fillers can be comprehensively utilized to further improve the overall performance of the coating. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The preparation method of the waterborne polyurethane / boron nitride composite is as follows: S11. Boric acid and urea were mixed in a mass ratio of 1:10 and added to water, and heated in a water bath at 85°C with stirring to obtain a BN precursor, and the BN precursor was heated to 550°C at a rate of 3°C / min and kept at that temperature for 3h to obtain flake boron nitride; S12. The flake boron nitride, urea and water were mixed and ball-milled at a speed of 500 r / min for 20 h. The mixed solution after ball milling was diluted and ultrasonically treated for 1 h, filtered and dried to obtain amino-modified boron nitride; S13. The amino-modified boron nitride is dispersed in acetone and uniformly dispersed by ultrasonication to obtain a boron nitride dispersion; S14. Mix polytetrahydrofuran ether diol and isophorone diisocyanate for reaction at a temperature of 95°C for 1.5 hours. After cooling to 80°C, add dimethylolpropionic acid and 1,4-butanediol for reaction for 2 hours. Cool again to 70°C, add dibutyltin dilaurate dropwise for reaction for 3 hours to obtain a polyurethane prepolymer. Then add a boron nitride dispersion and react for 1 hour, then cool to room temperature to obtain a waterborne polyurethane / boron nitride composite material, wherein the molar ratio of isophorone diisocyanate, polytetrahydrofuran ether diol, dimethylolpropionic acid and 1,4-butanediol is 5:1:1:2.6, and the content of boron nitride in the polyurethane prepolymer is 12wt%. Example 2 The preparation method of the waterborne polyurethane / boron nitride composite is as follows: S11. Boric acid and urea were mixed in a mass ratio of 1:14 and added to water, heated in a water bath at 90°C with stirring to obtain a BN precursor, and the BN precursor was heated to 500°C at a rate of 3°C / min and kept at that temperature for 3h to obtain flake boron nitride; S12. The flake boron nitride, urea and water were mixed and ball-milled at a speed of 800 r / min for 15 h. The mixed solution after ball milling was diluted and ultrasonically treated for 2 h, filtered and dried to obtain amino-modified boron nitride; S13. The amino-modified boron nitride is dispersed in acetone and uniformly dispersed by ultrasonication to obtain a boron nitride dispersion; S14. Mix polytetrahydrofuran ether diol and isophorone diisocyanate for reaction at a temperature of 90°C for 2.5 hours. After cooling to 80°C, add dihydroxymethylpropionic acid and 1,4-butanediol for reaction for 2 hours. Cool again to 70°C, add dibutyltin dilaurate dropwise for reaction for 3 hours to obtain a polyurethane prepolymer. Then add a boron nitride dispersion and react for 1.5 hours, then cool to room temperature to obtain a waterborne polyurethane / boron nitride composite material, wherein the molar ratio of isophorone diisocyanate, polytetrahydrofuran ether diol, dihydroxymethylpropionic acid and 1,4-butanediol is 10:2:2:5.5, and the content of boron nitride in the polyurethane prepolymer is 16wt%. Example 3 The preparation method of the waterborne polyurethane / boron nitride composite is as follows: S11. Boric acid and urea were mixed in a mass ratio of 1:12 and added to water, heated in a water bath at 90°C with stirring to obtain a BN precursor, and the BN precursor was heated to 530°C at a rate of 3°C / min and kept at that temperature for 3h to obtain flake boron nitride; S12. The flake boron nitride, urea and water were mixed and ball-milled at a speed of 600 r / min for 16 h. The mixed solution after ball milling was diluted and ultrasonically treated for 2 h, filtered and dried to obtain amino-modified boron nitride; S13. The amino-modified boron nitride is dispersed in acetone and uniformly dispersed by ultrasonication to obtain a boron nitride dispersion; S14. Mix polytetrahydrofuran ether diol and isophorone diisocyanate for reaction at a temperature of 95°C for 2 hours. After cooling to 80°C, add dihydroxymethylpropionic acid and 1,4-butanediol for reaction for 2 hours. Cool again to 70°C, add dibutyltin dilaurate dropwise for reaction for 3 hours to obtain a polyurethane prepolymer. Then add a boron nitride dispersion and react for 1.2 hours, then cool to room temperature to obtain a waterborne polyurethane / boron nitride composite material, wherein the molar ratio of isophorone diisocyanate, polytetrahydrofuran ether diol, dihydroxymethylpropionic acid and 1,4-butanediol is 8:1.6:1.6:4.5, and the content of boron nitride in the polyurethane prepolymer is 15wt%. Example 4 The preparation method of porous titanium dioxide loaded with copper ions or loaded with zinc ions comprises the following steps: S21. Add tetrabutyl titanate to ethanol, stir and disperse evenly, then add water, continue stirring until the tetrabutyl titanate is completely hydrolyzed, then add ammonium bicarbonate to the hydrolysis solution, the mass volume ratio of tetrabutyl titanate, ethanol, water and sodium bicarbonate is 3mL:10mL:50mL:1g, react at 190°C for 40h, and finally wash and dry to obtain nanoporous titanium dioxide powder; S22. The copper sulfate or zinc sulfate was added to a 0.5wt% aqueous solution of hydroxypropyl methylcellulose, and the mixture was stirred and dispersed to obtain a mixed solution, wherein the concentration of copper sulfate or zinc sulfate in the mixed solution was 3wt%; S23. Add nanoporous titanium dioxide to the mixed solution in step S22, and after ultrasonic dispersion, filter and dry to obtain porous titanium dioxide loaded with copper ions or loaded with zinc ions. Example 5 The preparation method of porous titanium dioxide loaded with copper ions or loaded with zinc ions comprises the following steps: S21. Add tetrabutyl titanate to ethanol, stir and disperse evenly, then add water, continue stirring until the tetrabutyl titanate is completely hydrolyzed, then add ammonium bicarbonate to the hydrolysis solution, the mass volume ratio of tetrabutyl titanate, ethanol, water and sodium bicarbonate is 2mL:20mL:100mL:1.8g, react at 170°C for 50h, and finally wash and dry to obtain nanoporous titanium dioxide powder; S22. The copper sulfate or zinc sulfate was added to a 1wt% aqueous solution of hydroxypropyl methylcellulose, and the mixture was stirred and dispersed to obtain a mixed solution, wherein the concentration of copper sulfate or zinc sulfate in the mixed solution was 1.5wt%; S23. Add nanoporous titanium dioxide to the mixed solution in step S22, and after ultrasonic dispersion, filter and dry to obtain porous titanium dioxide loaded with copper ions or loaded with zinc ions. Example 6 The preparation method of porous titanium dioxide loaded with copper ions or loaded with zinc ions comprises the following steps: S21. Add tetrabutyl titanate to ethanol, stir and disperse evenly, then add water, continue stirring until tetrabutyl titanate is completely hydrolyzed, then add ammonium bicarbonate to the hydrolysis solution, the mass volume ratio of tetrabutyl titanate, ethanol, water and sodium bicarbonate is 3mL:16mL:70mL:1.5g, react at 180°C for 45h, and finally wash and dry to obtain nanoporous titanium dioxide powder; S22. The copper sulfate or zinc sulfate was added to a 0.7wt% aqueous solution of hydroxypropyl methylcellulose, and the mixture was stirred and dispersed to obtain a mixed solution, wherein the concentration of copper sulfate or zinc sulfate in the mixed solution was 2.2wt%; S23. Add nanoporous titanium dioxide to the mixed solution in step S22, and after ultrasonic dispersion, filter and dry to obtain porous titanium dioxide loaded with copper ions or loaded with zinc ions. Example 7 A wear-resistant light-cured polyurethane coating, the polyurethane coating is a two-component polyurethane coating, the two-component polyurethane coating comprises component A and component B, wherein component A consists of the following components: waterborne polyurethane acrylate, waterborne polyurethane / boron nitride composite prepared in Example 1, photoinitiator, organosilicon defoamer, dispersant DIS-900, sodium lignin sulfonate, water; and component B consists of the following components: porous titanium dioxide loaded with copper ions or loaded with zinc ions prepared in Example 4 and ethanol; The preparation method of the waterborne polyurethane acrylate comprises: melting polyester diol, adding isophorone diisocyanate to react, then sequentially adding dimethylol propionic acid and hydroxyethyl acrylate, finally adding N,N-dimethylethanolamine to neutralize and form a salt, and finally adding water to react to obtain a waterborne polyurethane acrylate prepolymer, wherein the ratio of n(-NCO) to n(-OH) is 1.6; The application method of the above-mentioned wear-resistant light-cured polyurethane coating comprises the following steps: S1. Add the waterborne polyurethane acrylate in component A to water according to the following weight parts, and then add the waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 in sequence, mix and stir evenly to obtain coating X, In the component A, 120 parts of waterborne polyurethane acrylate, 40 parts of waterborne polyurethane / boron nitride composite, 2 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 0.3 parts of organosilicon defoamer, 0.2 parts of dispersant DIS-900, and 40 parts of water; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 are added in sequence, mixed and stirred to obtain coating Y; In the component A, 120 parts of waterborne polyurethane acrylate, 60 parts of waterborne polyurethane / boron nitride composite, 2 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 0.3 parts of organosilicon defoamer, 0.2 parts of dispersant DIS-900, 10 parts of sodium lignin sulfonate, and 40 parts of water; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z, wherein the porous titanium dioxide loaded with copper ions or loaded with zinc ions is 5 parts and ethanol is 90 parts; S4. Apply coating X on the substrate with a coating amount of 80 g / m 2 After UV curing, coating Y is applied on the substrate with a coating amount of 55g / m 2 Finally, apply coating Z with a coating amount of 20g / m 2 , and then cured by ultraviolet radiation to obtain a wear-resistant coating. Example 8 A wear-resistant light-cured polyurethane coating, the polyurethane coating is a two-component polyurethane coating, the two-component polyurethane coating comprises component A and component B, wherein component A consists of the following components: waterborne polyurethane acrylate, waterborne polyurethane / boron nitride composite prepared in Example 2, photoinitiator, organosilicon defoamer, dispersant DIS-900, sodium lignin sulfonate, water; and component B consists of the following components: porous titanium dioxide loaded with copper ions or loaded with zinc ions prepared in Example 5 and ethanol; The preparation method of the waterborne polyurethane acrylate comprises: melting polyester diol, adding isophorone diisocyanate to react, then sequentially adding dimethylol propionic acid and hydroxyethyl acrylate, finally adding N,N-dimethylethanolamine to neutralize and react with salt, and finally adding water to react with hydration to obtain a waterborne polyurethane acrylate prepolymer, wherein the ratio of n(-NCO) to n(-OH) is 1.55; The application method of the above-mentioned wear-resistant light-cured polyurethane coating comprises the following steps: S1. Add the waterborne polyurethane acrylate in component A to water according to the following weight parts, and then add the waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 in sequence, mix and stir evenly to obtain coating X, In the component A, 180 parts of waterborne polyurethane acrylate, 40 parts of waterborne polyurethane / boron nitride composite, 5 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 1.5 parts of organosilicon defoamer, 1.5 parts of dispersant DIS-900, and 70 parts of water; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 are added in sequence, mixed and stirred to obtain coating Y; In the component A, 180 parts of waterborne polyurethane acrylate, 60 parts of waterborne polyurethane / boron nitride composite, 5 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 1.5 parts of organosilicon defoamer, 1.5 parts of dispersant DIS-900, 20 parts of sodium lignin sulfonate and 70 parts of water are contained; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z, wherein the porous titanium dioxide loaded with copper ions or loaded with zinc ions is 10 parts and ethanol is 100 parts; S4. Apply coating X on the substrate at a coating amount of 65 g / m 2 After UV curing, coating Y is applied on the substrate with a coating amount of 70g / m 2 Finally, apply coating Z with a coating amount of 20g / m 2 , and then cured by ultraviolet radiation to obtain a wear-resistant coating. Example 9 A wear-resistant light-cured polyurethane coating, the polyurethane coating is a two-component polyurethane coating, the two-component polyurethane coating comprises component A and component B, wherein component A consists of the following components: waterborne polyurethane acrylate, waterborne polyurethane / boron nitride composite prepared in Example 3, photoinitiator, organosilicon defoamer, dispersant DIS-900, sodium lignin sulfonate, water; and component B consists of the following components: porous titanium dioxide loaded with copper ions or loaded with zinc ions prepared in Example 6 and ethanol; The preparation method of the waterborne polyurethane acrylate comprises: melting polyester diol, adding isophorone diisocyanate to react, then sequentially adding dimethylol propionic acid and hydroxyethyl acrylate, finally adding N,N-dimethylethanolamine to neutralize and form a salt, and finally adding water to react to obtain a waterborne polyurethane acrylate prepolymer, wherein the ratio of n(-NCO) to n(-OH) is 1.5; The application method of the above-mentioned wear-resistant light-cured polyurethane coating comprises the following steps: S1. Add the waterborne polyurethane acrylate in component A to water according to the following weight parts, and then add the waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 in sequence, mix and stir evenly to obtain coating X, In the component A, 140 parts of waterborne polyurethane acrylate, 45 parts of waterborne polyurethane / boron nitride composite, 3 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 0.5 parts of organosilicon defoamer, 0.5 parts of dispersant DIS-900, and 50 parts of water; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 are added in sequence, mixed and stirred to obtain coating Y; In the component A, 140 parts of waterborne polyurethane acrylate, 55 parts of waterborne polyurethane / boron nitride composite, 3 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 0.5 parts of organosilicon defoamer, 0.5 parts of dispersant DIS-900, 10 parts of sodium lignin sulfonate and 50 parts of water are included; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z, wherein the porous titanium dioxide loaded with copper ions or loaded with zinc ions is 8 parts and ethanol is 90 parts; S4. Apply coating X on the substrate with a coating amount of 70 g / m 2 After UV curing, coating Y is applied on the substrate with a coating amount of 65g / m 2 Finally, apply coating Z with a coating amount of 20g / m 2 , and then cured by ultraviolet radiation to obtain a wear-resistant coating. Example 10 A wear-resistant light-cured polyurethane coating, the polyurethane coating is a two-component polyurethane coating, the two-component polyurethane coating comprises component A and component B, wherein component A consists of the following components: waterborne polyurethane acrylate, waterborne polyurethane / boron nitride composite prepared in Example 3, photoinitiator, organosilicon defoamer, dispersant DIS-900, sodium lignin sulfonate, water; and component B consists of the following components: porous titanium dioxide loaded with copper ions or loaded with zinc ions prepared in Example 6 and ethanol; The preparation method of the waterborne polyurethane acrylate comprises: melting polyester diol, adding isophorone diisocyanate to react, then sequentially adding dimethylol propionic acid and hydroxyethyl acrylate, finally adding N,N-dimethylethanolamine to neutralize and form a salt, and finally adding water to react to obtain a waterborne polyurethane acrylate prepolymer, wherein the ratio of n(-NCO) to n(-OH) is 1.5; The application method of the above-mentioned wear-resistant light-cured polyurethane coating comprises the following steps: S1. Add the waterborne polyurethane acrylate in component A to water according to the following weight parts, and then add the waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 in sequence, mix and stir evenly to obtain coating X, In the component A, 160 parts of waterborne polyurethane acrylate, 45 parts of waterborne polyurethane / boron nitride composite, 4 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 1.2 parts of organosilicon defoamer, 1.2 parts of dispersant DIS-900, and 60 parts of water; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 are added in sequence, mixed and stirred to obtain coating Y; In the component A, 160 parts of waterborne polyurethane acrylate, 55 parts of waterborne polyurethane / boron nitride composite, 4 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 1.2 parts of organosilicon defoamer, 1.2 parts of dispersant DIS-900, 20 parts of sodium lignin sulfonate, and 60 parts of water; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z, wherein the porous titanium dioxide loaded with copper ions or loaded with zinc ions is 10 parts and ethanol is 100 parts; S4. Apply coating X on the substrate with a coating amount of 75g / m 2 After UV curing, coating Y is applied on the substrate with a coating amount of 60g / m 2 Finally, apply coating Z with a coating amount of 20g / m 2 , and then cured by ultraviolet radiation to obtain a wear-resistant coating. Comparative Example 1 The difference between Comparative Example 1 and Example 10 is that the content of waterborne polyurethane / boron nitride in step S1 is higher than that in step S2, specifically: The application method of the wear-resistant light-cured polyurethane coating comprises the following steps: S1. Add the waterborne polyurethane acrylate in component A to water according to the following weight parts, and then add the waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 in sequence, mix and stir evenly to obtain coating X, In the component A, 160 parts of waterborne polyurethane acrylate, 60 parts of waterborne polyurethane / boron nitride composite, 4 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 1.2 parts of organosilicon defoamer, 1.2 parts of dispersant DIS-900, and 60 parts of water; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, silicone defoamer and dispersant DIS-900 are added in sequence, mixed and stirred to obtain coating Y; In the component A, 160 parts of waterborne polyurethane acrylate, 30 parts of waterborne polyurethane / boron nitride composite, 4 parts of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone, 1.2 parts of organosilicon defoamer, 1.2 parts of dispersant DIS-900, 20 parts of sodium lignin sulfonate, and 60 parts of water; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z, wherein the porous titanium dioxide loaded with copper ions or loaded with zinc ions is 10 parts and ethanol is 100 parts; S4. Apply coating X on the substrate with a coating amount of 75g / m 2 After UV curing, coating Y is applied on the substrate with a coating amount of 60g / m 2 Finally, apply coating Z with a coating amount of 20g / m 2 , and then cured by ultraviolet radiation to obtain a wear-resistant coating. Comparative Example 2 The difference between Comparative Example 2 and Example 10 is that sodium lignin sulfonate is not added in step S2. Comparative Example 3 The difference between Comparative Example 3 and Example 10 is that coating material Z is not applied. Comparative Example 4 The difference between Comparative Example 4 and Example 10 is that coating materials Y and Z are applied, and coating material X is not applied. Comparative Example 5 The difference between Comparative Example 5 and Example 10 is that spherical boron nitride is used instead of flake BN. According to the above-mentioned embodiments and comparative examples and in combination with the application method, a wear-resistant light-cured polyurethane coating was obtained, and conventional performance (substrate adhesion (100 grids), coating hardness), wear resistance and Vickers hardness tests were performed. The conventional properties of the coating are tested using conventional coating testing methods; The Vickers hardness of the coating was tested using a hardness tester, the applied load was 0.0981N, and the hardness value (Hv) was measured; The wear resistance of the coating was tested using a flat abrasion tester. The experimental conditions were: the applied load was 294N, 600# abrasive paper was used, 4800 flat grindings were performed, the wear mark was 30mm×12mm, and the wear rate was calculated. Adhesion to substrate (100 grids) Vickers hardness Hv(MPa) Wear rate (%) Example 7 5B 122.1 0.52 Example 8 5B 118.9 0.48 Example 9 5B 116.7 0.55 Example 10 5B 121.5 0.45 Comparative Example 1 4B 119.2 0.57 Comparative Example 2 4B 120.3 1.54 Comparative Example 3 5B 108.4 1.48 Comparative Example 4 4B 112.7 0.71 Comparative Example 5 5B 118.8 0.89 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A wear-resistant light-cured polyurethane coating, characterized in that: The polyurethane coating is a two-component polyurethane coating, and the two-component polyurethane coating comprises component A and component B, wherein component A is composed of the following components in parts by weight: 120-180 parts of waterborne polyurethane acrylate 40-60 parts of waterborne polyurethane / boron nitride compound Photoinitiator 2-5 parts Additives 0.5-3 parts Sodium lignin sulfonate 10-20 parts 40-70 parts of water; The component B is composed of the following important components: 5-10 parts of porous titanium dioxide loaded with copper ions or loaded with zinc ions Ethanol 90-100 parts; The waterborne polyurethane acrylate is any one or two of polyether waterborne polyurethane acrylate and polyester waterborne polyurethane acrylate; The photoinitiator is any one of 2-hydroxy-4'(2-hydroxyethoxy)-2-methylpropiophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone or a mixture of more than one thereof; The auxiliary agent includes any one of a defoamer, a formaldehyde removal additive, an antibacterial additive, an anti-settling agent, a matting agent, a hand wax, and a dispersant, or a mixture of more than one of the above.
2. The wear-resistant light-curing polyurethane coating according to claim 1, characterized in that: The preparation method of the waterborne polyurethane / boron nitride composite is as follows: S11. Boric acid and urea are mixed in a mass ratio of 1:10-14 and added to water, heated in a water bath at 85-90° C. with stirring to obtain a BN precursor, and the BN precursor is reacted at high temperature to obtain flake boron nitride; S12. The flake boron nitride, urea and water were mixed and ball-milled at a speed of 500-800 r / min for 15-20 h. The mixed solution after ball milling was diluted and ultrasonically treated for 1-2 h, filtered and dried to obtain amino-modified boron nitride; S13. The amino-modified boron nitride is dispersed in acetone and uniformly dispersed by ultrasonication to obtain a boron nitride dispersion; S14. Mix polytetrahydrofuran ether diol and isophorone diisocyanate for reaction at a temperature of 90-95°C for 1.5-2.5 hours. After cooling to 80°C, add dihydroxymethylpropionic acid and 1,4-butanediol for reaction for 2 hours. Cool again to 70°C, add dibutyltin dilaurate dropwise for reaction for 3 hours to obtain a polyurethane prepolymer. Then add a boron nitride dispersion, react for 1-1.5 hours, and then cool to room temperature to obtain a waterborne polyurethane / boron nitride composite material.
3. The wear-resistant light-curing polyurethane coating according to claim 1, characterized in that: The preparation method of the porous titanium dioxide loaded with copper ions or loaded with zinc ions comprises the following steps: S21. Add tetrabutyl titanate to ethanol, stir and disperse evenly, then add water, continue stirring until the tetrabutyl titanate is completely hydrolyzed, and then add ammonium bicarbonate to the hydrolysis solution, the mass volume ratio of tetrabutyl titanate, ethanol, water and sodium bicarbonate is 2-4mL:10-20mL:50-100mL:1-2g, react at 170-190°C for 40-50h, and finally wash and dry to obtain nanoporous titanium dioxide powder; S22. The copper sulfate or zinc sulfate is added to a 0.5-1wt% aqueous solution of hydroxypropyl methylcellulose, and the mixture is stirred and dispersed to obtain a mixed solution, wherein the concentration of the copper sulfate or zinc sulfate in the mixed solution is 1-3wt%; S23. Add nanoporous titanium dioxide to the mixed solution in step S22, and after ultrasonic dispersion, filter and dry to obtain porous titanium dioxide loaded with copper ions or loaded with zinc ions.
4. The method for applying the wear-resistant light-curing polyurethane coating according to claim 1, characterized in that: The following steps are involved: S1. The aqueous polyurethane acrylate in component A is added to water in parts by weight, and then the aqueous polyurethane / boron nitride complex, the photoinitiator and the additive are added successively, and the mixture is stirred to obtain a coating X; S2. The sodium lignin sulfonate in component A is added to water in parts by weight, stirred and mixed, and then waterborne polyurethane acrylate, waterborne polyurethane / boron nitride complex, photoinitiator and additives are added, mixed and stirred to obtain coating Y; S3. The porous titanium dioxide loaded with copper ions or loaded with zinc ions is added to ethanol and ultrasonically dispersed to obtain a coating Z; S4. Apply coating X on the substrate at a coating amount of 45-125 g / m 2 After UV curing, the coating Y is applied to the substrate at a coating amount of 35-85g / m 2 Finally, coating Z is applied and cured by ultraviolet radiation again to obtain a wear-resistant coating.
5. The method for applying the wear-resistant light-curing polyurethane coating according to claim 4, characterized in that: The substrate comprises: Wood board, stone plastic composite floor; Among them, wooden boards include: a: solid wood flooring; b: any other core material, base material but with solid wood flooring as the surface layer; stone plastic composite flooring is: a solid base layer with a high-density, high-fiber mesh structure composed of stone powder, and the surface is covered with a wear-resistant polyurethane coating.
6. The wear-resistant light-cured polyurethane coating according to claim 2, characterized in that: The parameters of the high temperature reaction in step S11 are: heating to 500-550° C. at 3° C. / min and keeping the temperature for 3 hours.
7. The wear-resistant light-cured polyurethane coating according to claim 2, characterized in that: In the step S14, the molar ratio of isophorone diisocyanate, polytetramethylene ether glycol, dimethylol propionic acid and 1,4-butanediol is 5-10:1-2:1-2:2.6-5.
5.
8. The wear-resistant light-cured polyurethane coating according to claim 2, characterized in that: In the step S14, the content of boron nitride in the polyurethane prepolymer is 12-16 wt %.
Citation Information
Patent Citations
Preparing method for nanoscale porous titanium dioxide hollow spheres
CN105565375A
Ultraviolet curing heat-resistant and yellowing-resistant coating and preparation method thereof
CN116751509A
High-temperature-resistant flame-retardant polyurethane foam with self-repairing performance and preparation method thereof
CN117229473A
Cited By
High-hardness pet-scratching-resistant optical window film and preparation method thereof
CN120842659A